Hyaluronic acid synthase 2 dysfunction exacerbates elastase-induced neutrophilic airway inflammation and emphysema in mice - Nishino, Kengo; Kiwamoto, Takumi; Matsuyama, Masashi; Wei, Zhenting; Matsumura, Sosuke; Kuramoto, Kenya; Yabuuchi, Yuki; Yazaki, Kai; Yoshida, Kazufumi; Matsuno, Yosuke; Morishima, Yuko; Hizawa, Nobuyuki (Frontiers in Immunology, 2025)
Chronic obstructive pulmonary disease (COPD) is a progressive inflammatory lung disorder primarily caused by prolonged exposure to harmful substances, such as cigarette smoke. Hyaluronic acid synthase 2 (HAS2) synthesizes high-molecular-weight hyaluronic acid (HMW-HA), which has anti-inflammatory properties. Previous studies have revealed that HAS2 dysfunction may exacerbate COPD. However, the specific impact of HAS2 on pulmonary emphysema progression remains unclear. Therefore, this study examined whether HAS2 dysfunction worsens airway inflammation and emphysema in a mouse COPD model. Has2 heterozygous-deficient (Has2+/−) mice and their wild-type (WT) littermates were evaluated using a porcine pancreatic elastase (PPE)-induced COPD model. After the administration of PPE, the Has2+/− mice exhibited a significant increase in total cell and neutrophil counts in the bronchoalveolar lavage fluid samples compared with the WT mice. Further, the Has2+/− mice presented with enhanced emphysema development on histological analyses, with higher mean linear intercept values relative to the WT mice. The PPE-stimulated Has2+/− mice also had increased G-CSF levels and tumor growth factor-beta (TGF-β) attenuation in the lungs. RNA-sequencing analysis revealed that PPE stimulation promoted the synthesis of HMW-HA and TGF-β signaling. Gene Ontology analysis using Has2+/− mice-specific differentially expressed genes showed that the genes associated with the pathways that promote the negative regulation of the TGF-β receptor signaling pathway were activated after the administration of PPE. Therefore, Has2 dysfunction exacerbates neutrophilic airway inflammation and emphysema, thereby underscoring the protective role of HAS2 in a PPE-induced emphysema model. The exacerbated response may involve G-CSF- and TGF-β-related signaling pathways. These findings may contribute to the development of novel therapeutic strategies for COPD management.